Numerical investigation for turbulent heat transfer of TiO2–SiO2 nanofluids with wire coil inserts. (16th February 2019) - Hamid, K. Abdul; Azmi, W. H.; Mamat, Rizalman; Mohamad, M. S.; Sharma, K. V.
Abstract: A numerical model has been developed for turbulent flow of hybrid nanofluids in a tube with wire coil inserts. The model was developed from van Driest eddy diffusivity equation. The model can be implemented with the consideration of new variables in eddy diffusivity of momentum and heat by using the coefficient, K and Prandtl index, ζ, respectively. The numerical analysis are undertaken for wide range of Reynolds number, different volume concentration, ϕ and various pitch ratio, P/D of wire coil. The numerical results were validated with the experimental data of TiO2 –SiO2 nanofluids undertaken for wide range of Reynolds number and volume concentration. The final regression models of coefficient K and Prandtl index ζ were developed as a function of Reynolds number, Re or dimensionless radius, R +, volume concentration, ϕ and pitch ratio, P/D . A good agreement between the experimental data and numerical model indicating the validity of the numerical model for hybrid nanofluids with wire coil inserts. The numerical analysis was proved that the hybrid nanofluids contributes to higher Nusselt number and thus have better heat transfer performance compared to single nanofluids.